Approximation: Documentary, history and the staging of reality. (1st April 2013) - Bruzzi, Stella
The article explores the idea of 'approximation': the layered understanding of historical moments and events via works whose aim is to approximate reality and all its ramifications, rather than more straightforwardly to represent it. It sets out to discuss the terrorist attacks on the World Trade Center, 11 September 2001, through juxtaposition with representations and re-enactments of their most notable and traumatic antecedent, namely the assassination of President John Kennedy, 22 November 1963. After briefly examining how the two events are brought together in the television series Mad Men, issues of history, representation and art are analyzed in more detail in relation to Abraham Zapruder's home movie of the assassination, Bruce Conner's Report (1963–1967) and Ant Farm and T. R. Uthco's The Eternal Frame (1976).